The The Views of Music Education Students from the Bachelor’s Degree in Primary Education on the Impact that COVID-19 had on the Musical Tale as a Training Activity - Syroyid Syroyid, Bohdan; De Moya Martínez, María del Valle (Rastros Rostros, 2021)
Introduction. In Spain, due to COVID-19, a state of alarm was declared forcing a change from face-to-faceteaching to an online model. This article reflects on this sudden transition and its impact on the didactic resource of the musical tale, understood as a story or a play with musical elements, an interdisciplinary approachaimed at acquiring key competences.Methodology. In the third year of the bachelor’s degree in Primary Education, students conducted an onlinegroup project based on a musical tale, which in previous editions was performed face-to-face. A sample of 86participants from a population of 116 students of the Faculty of Education in Albacete (uclm) was surveyed toexamine students’ views on this digital transition.Results. The efforts that Musical Education faculty made for smoothly transitioning to an online methodology was positively valued, although a preference in favor of face-to-face teaching over online teaching wasreported. Benefits and drawbacks were identified in the staging of a musical fable in an online format, andother aspects that highlighted its didactic value. 90.1 % of the surveyed students expressed feeling adequatelyprepared to take this activity to a school class.Conclusions. The musical fable as a didactic resource was positively valued by students, and its implementation to the online format was satisfactory.
Keywords: tale; musical accompaniment; pedagogy; eacher competences; primary education; arts education; Spain